A quantitative study of test anxiety and its influencing factors among medical and dental students. Issue 2 (April 2021) - Nazir, Muhammad A.; Izhar, Faisal; Talal, Ahmad; Sohail, Zaid B.; Majeed, Abdul; Almas, Khalid
الملخص: أهداف البحث: أجريت هذه الدراسة لتقييم قلق الإختبار وعوامله المؤثرة على طلاب الطب وطب الأسنان. طرق البحث: أجريت هذه الدراسة المقطعية المستعرضة بين الطلاب من ثلاث كليات للطب وطب الأسنان خاصة وعامة في إقليم البنجاب في الباكستان. شمل الاستطلاع بيانات عن الملف الديموغرافي للمشاركين في الدراسة باستخدام مخزون قلق الاختبار بواسطة سبيلبرجر. النتائج: شملت الدراسة ٦٨٠ طالبا مع متوسط ٢٠.٩٣±١.٧٦عاما. سجل تقريبا نصف العينة (٥١.٨٪) درجة عالية في قلق الاختبار (مخزون قلق الاختبار <٤٥)، وكان متوسط درجة مخزون قلق الاختبار أعلى قليلا عند طلاب الأسنان (٤٧.٧٥±١١.٤٥) عن طلاب الطب (٤٦.٤٢±١٢.٧٩). حصلت الطالبات درجة أعلى بكثير في متوسط درجة مخزون قلق الاختبار (٤٨.٤٥±١٢.٧٩) من الطلاب (٤١.٨٥±٨.٩١). أظهر الطلاب من الكليات الخاصة أعلى درجة من قلق الاختبار (٥٠.١٥±١٣.٢٣) عن الطلاب في الكليات العامة (٤٢.٨٨±٩.٧). وأظهر الطلاب الذين تخرج والديهم من كلية أو جامعة زيادة قلق الاختبار بشكل ملحوظ عن الطلاب الذين لم يحصل والديهم على تعليم. الجنس الأنثوي (النسبة الفردية المعدلة ٢.١٠، ٩٥٪ فاصل الثقة: ١.٣٧، ٣.٢٢)، طالب الكلية الخاصة (النسبة الفردية المعدلة ٢.٨٨، ٩٥٪ فاصل الثقة: ١.٩٠، ٤.٣٨) وكان حصول الأم على تعليم في الكلية أو جامعي مرتبطا بأعلى قلق الاختبار (النسبة الفردية المعدلة ٢.٠٥، ٩٥٪ فاصل الثقة: ١.٢٥، ٣.٣٥). الاستنتاجات: في مجموعة دراستنا، كان قلق الاختبار شائعا بين طلاب الطب وطب الأسنان. وكان الجنس الأنثوي، الطلاب من الكلية الخاصة، والتعليم العالي للأمهات مرتبط بشكل كبير بقلق شديد من الاختبار. يمكن لنتائج هذه الدراسة أن ترشد تطوير برنامج يمكن أن يقلل من قلق الاختبار لدى الطلاب ويحتمل أن يحسن تعليمهم. Abstract: Objective: The study was conducted to assess test anxiety and its influencing factors on medical and dental students. Methods: A cross-sectional study was conducted among students from three private and public medical and dental colleges in the Punjab province of Pakistan. The survey included statements about the demographic profile of the study participants and used the Test Anxiety Inventory (TAI) by Spielberger. Results: The study included 680 students with a mean age of 20.93 ± 1.76 years. About half the sample (51.8%) scored high on test anxiety (TAI score > 45), and the mean TAI score was slightly higher for the dental (47.75 ± 11.45) than medical students (46.42 ± 12.79). Female students had a significantly higher mean TAI score (48.45 ± 12.79) than male students (41.85 ± 8.91; p  < 0.001). The students from private colleges had a significantly greater test anxiety score (50.15 ± 13.23) than students from public colleges (42.88 ± 9.7; p  < 0.001). Students whose parents were graduates from a college or university perceived significantly increased test anxiety than those of parents with no/school education ( p  < 0.001). A female gender (adjusted odds ratio (AOR) 2.10, 95% CI:1.37, 3.22), being a private college student (AOR 2.88, 95% CI:1.90, 4.38), and having a mother with a college or university education (AOR 2.05, 95% CI: 1.25, 3.35) were significantly associated with high on test anxiety. Conclusion: In our study cohort, test anxiety was common among medical and dental students. A female gender, being a student from a private college, and having a mother with a high education were significantly associated with high test anxiety. The study findings may guide the development of programs that can reduce students' test anxiety and potentially improve their education.